Insensitivity to verb conjugation patterns in French children with SLI. (1st February 2018) - Royle, Phaedra; St-Denis, Ariane; Mazzocca, Patrizia; Marquis, Alexandra
ABSTRACT: Specific language impairment (SLI) is characterised by persistent difficulties that affect language abilities in otherwise normally developing children (Leonard, 2014). It remains challenging to identify young children affected by SLI in French. We tested oral production of the passé composé tense in 19 children in kindergarten and first grade with SLI aged from 5;6 to 7;4 years. All children were schooled in a French environment, but with different linguistic backgrounds. We used an Android application, Jeu de verbes (Marquis et al., 2012), with six verbs in each of four past participle categories (ending in -é, -i, -u, and other irregulars). We compared their results and error types to those of control children (from Marquis, 2012–2014) matched for gender, age, languages spoken at home, and parental education. Results show that children with SLI do not master the passé composé in the same way as typical French children do, at later ages than previously shown in the literature. This task shows potential for oral language screening in French-speaking children in kindergarten and first grade, independently of language background.